The age at first cutaneous manifestation of psoriasis as a prognostic factor in the timing of psoriatic arthritis diagnosis - Elena V. Bogdanova (Vestnik Dermatologii i Venerologii, 2022)
Background. Psoriatic arthritis is a chronic inflammatory disease of joints, spine and enthesis, which develops in 640% of patients with psoriasis and has a significant impact on the quality of life of patients.